1991
DOI: 10.1007/bf00966086
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal expression of glutamate decarboxylases in developing rat cerebellum

Abstract: The recent identification of two genes encoding distinct forms of the GABA synthetic enzyme, glutamate decarboxylase (GAD), raises the possibility that varying expression of the two genes may contribute to the regulation of GABA production in individual neurons. We investigated the postnatal development the two forms of GAD in the rat cerebellum. The mRNA for GAD67, the form which is less dependent on the presence of the cofactor, pyridoxal phosphate (PLP), is present at birth in presumptive Purkinje cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 22 publications
7
47
1
Order By: Relevance
“…The prolonged development of GAD67-and GAD65-positive puncta (synaptic terminals) agrees with quantitative results on GABA synapses that increase dramatically from very low levels at birth to reach adult numbers after 3 weeks of age (Micheva and Beaulieu, 1996). The delayed development of GAD65 relative to GAD67 has been observed in other systems (Greif et al, 1991(Greif et al, , 1992Guo et al, 1997).…”
Section: Prolonged Maturation Of Somatosensory Cortical Gad Immunoreasupporting
confidence: 75%
See 1 more Smart Citation
“…The prolonged development of GAD67-and GAD65-positive puncta (synaptic terminals) agrees with quantitative results on GABA synapses that increase dramatically from very low levels at birth to reach adult numbers after 3 weeks of age (Micheva and Beaulieu, 1996). The delayed development of GAD65 relative to GAD67 has been observed in other systems (Greif et al, 1991(Greif et al, , 1992Guo et al, 1997).…”
Section: Prolonged Maturation Of Somatosensory Cortical Gad Immunoreasupporting
confidence: 75%
“…A plausible hypothesis is that the two GADs play distinct roles during the maturation of the central nervous system. In support of this idea, recent evidence has shown that the two isoforms are expressed differentially during postnatal development in several brain areas (Greif et al, 1991(Greif et al, , 1992Guo et al, 1997). Additionally, the developmental kinetics of the two GADs and an alternatively spliced variant of GAD67 parallel neurogenesis and differentiation of the embryonic rat spinal cord (Behar et al, 1993;Somogyi et al, 1995).…”
mentioning
confidence: 84%
“…In contrast, GABAergic synapses (synapses per neuron) expand rapidly from P10 to P30 (Micheva and Beaulieu, 1996). The observed increase in V cyc(GABA) (B7 Â ), V TCA(GABA) (B5 Â ), and V GAD (B5.5 Â ) closely parallels the reported percentage increase in total GAD activity of 400% to 470% in the neocortex from P10 to adulthood (Balcar et al, 1992), becoming increasingly associated (65-kd isoform) with nerve terminals (Greif et al, 1991). Thus, the increase in GABA-related fluxes between P10 and P30 appears to be similar to the expansion in the number of inhibitory synapses.…”
Section: Comparison Of Glutamatergic and Gabaergic Neurotransmission supporting
confidence: 66%
“…However, they are equipped with the appropriate vesicular transporter (VIAAT) to release GABA in a paracrine manner, and, because the nearby Purkinje cells express GABA A and GABA B receptors (Laurie et al, 1992;Fritschy et al, 1994;Lujan and Shigemoto, 2006), the released GABA might elicit a functional response in newborn Purkinje cells. Thus, postnatal Purkinje cells may respond to GABA release far before the formation of the first synapses with basket fibers (P7; Ango et al, 2004;present study) and before initiation of the expression of GABAergic markers other than VIAAT (McLaughlin et al, 1975;Greif et al, 1991;Yan and Ribak, 1998;Rosina et al, 1999;Takayama and Inoue, 2005).…”
Section: Discussionmentioning
confidence: 98%